Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

Transforming social media sentiment analysis with generative large language models: A case study from the cultured meat debate - Tianli Chen; Leona Yi-Fan Su; Yee Man Margaret Ng; Matthew J. Stasiewicz; Yi-Cheng Wang (Food Quality and Preference, 2026)

Bacillus subtilis is crucial for the normal growth of mycelium for Stropharia rugosoannulata - Yu Tian; Man Cui; Suyue Zheng; Nuolin Yang; Qinghao Fan; Jinwei Zhang; Gaige Shao; Ruiying Zhang (Fungal Biology, 2026)

Corncob biorefinery: XOS via extrusion–microwave hydrolysis and carbon/MoS2 catalysts from residue - Jiakang Liang; Jingyi Han; Ziwei Zhu; Xingyu Fan; Yagoub Abu El-Gasim A; Man Zhou; Haoxin Li; Li Chen; Xiaojie Yu; Cunshan Zhou (Biomass and Bioenergy, 2026)

Wastewater treatment process optimization in stochastic game based on multiagent deep reinforcement learning - Guanghua Wang; Xingyu Wang; Fan Luo; Yi Man; Zhenglei He; Sai Liang; Zhifeng Yang (Water Research, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Myricetin activates innate antiviral immunity during PRRSV infection in MARC-145 cells - Aiyang Wang; Weizhen Chen; Bo Wang; Man Tong; Xing Feng; Shaojun He; Hongjie Fan; Liujun Zhang (Veterinary Immunology and Immunopathology, 2026)

A systematic review of coal-based adsorbents: preparation, properties and applications - Bo Lv; Xueyao Chen; Wen Fan; Yutong Jiao; Man Wang; Baolin Xing (Journal of Water Process Engineering, 2026)

Boundary-layer deflection and convergence mechanics of heterogeneous jets in interactive cascade ventilation - Han Li; Ruoyi Liu; Nana Li; Man Fan; Zhijun Ren; Xiangfei Kong (Building and Environment, 2026)

Synergistic effect of high-voltage alternating and static electric fields on quality maintenance of partially frozen Litopenaeus vannamei via stabilization of protein structure - Zekai Fan; Chen Li; Bing Chen; Ning Wang; Man Fu; Donglei Luan; Zunying Liu; Kaining Han; Shiyuan Dong (Food Chemistry, 2026)

Epigenetic impacts of the acaricide flumethrin on honeybees (Apis mellifera) - Xue Wang; Suzhen Qi; Mu Ding; Wei Zhang; Aidi Huang; Changlu Sun; Man Fan; Liming Wu; Miao Wang (Environmental Pollution, 2026)

Acidobacteria taxa mediate the biphasic temperature sensitivity of soil organic carbon in restored ecosystems - Man Cheng; Weiqi Feng; Minggang Xu; Shaoshan An; Lichao Fan; Katharina Maria Keiblinger; Shanping Wan; Zonglin Shi; Yongli Wen; Dong Liu (Applied Soil Ecology, 2026)

Different environmental controls on archaeal and bacterial GDGT distributions in Chinese peatlands - Huan Yang; Lijia Zhang; Weihua Ding; Zhengyu Xia; Yi Man; Linfeng Gong; Xianyu Huang; Xinyue Dang; Jiachen Fan; Jie Wu; Miao Huang (Organic Geochemistry, 2026)

Asperhydrindane A, a new hydrindane derivate isolated from a mangrove-derived fungi Aspergillus terreus GXIMD 03158 - Yue Jiang; Fan An; Yu-Man Gan; Kai Liu; Yong-Hong Liu; Cheng-Hai Gao; Pei Cao; Xiang-Xi Yi; Meng Bai (Natural Product Research, 2026)

Gingerols and their derivatives from ginger oleoresin and the anti-melanogenic effect in IBMX-stimulated B16F10 melanoma cells - Jiarui Wu; Siyang Fan; Man Yang; Huali Wu; Fujiang Guo; Kaixian Chen; Liuqiang Zhang; Yiming Li (Phytochemistry, 2026)

Construction of recombinant Lactococcus lactis expressing VP1 from duck hepatitis a virus types 1 and 3 and evaluation of its immune effect - Yafei Qin; Yaru Fan; Meijuan Zhang; Saisai Zhao; Xinhong Man; Dalin He; Youxiang Diao; Junxun Li; Jingdong Hu; Yi Tang (Veterinary Research Communications, 2026)

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

Curdlan modulates potato starch gelatinization and gelation: Mechanisms of interaction, structural enhancement, and texture improvement in hydrogel foods - Yongxin Liu; Xinyi Li; Liya Chen; Fan Feng; Chang Sun; Yingchao Xu; Xinyu Sun; Man Li; Qingjie Sun; Xingfeng Xu; Fengwei Xie; Yanfei Wang (Food Hydrocolloids, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

A histone methylation reader suppresses both disease resistance and tillering by facilitating H3K9me1-mediated gene silencing in rice - Fengfeng Fan; Manman Liu; Huanran Yuan; Nannan Li; Mingxing Cheng; Xiong Luo; Yu Guo; Ayaz Ahmad; Meng Cai; Fengfeng Si; Zihan Yang; Man Wang; et al. (Molecular Plant, 2026)

Fabrication of sulfonated polypropylene melt-blown cloth-supported L-cysteine-functionalized defective Ce-Uio-66-NH₂ composites with enhanced Cu(Ⅱ) sequestration performance - Yi-Man Sun; Xue-Qi Fan; Song-Yang Yue; Le Tao; Shu-Xia Guan; De-Bin Ji (Journal of Environmental Chemical Engineering, 2026)

Magnetic iron oxide-loaded coal-based activated carbon for Enhanced copper (II) removal: Batch and fluidized bed studies - Wen Fan; Bo Lv; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Fuel, 2026)

Synergistic enhancement of gelatin-chitosan films with vanillin Schiff base and ZnO for effective strawberry preservation - Ziwei Zhu; Jiakang Liang; Cunshan Zhou; Ke Huang; Xingyu Fan; Man Zhou; Baoguo Xu; Chengxia Huang; Haoxin Li; Haile Ma; Li Chen (Food Control, 2026)

Enhanced photocatalytic uranium(VI) removal via oxygen vacancy-assisted Z-scheme SPC-Bi/Bi2WO6 with plasmonic Bi activation - Le Tao; Xue-Qi Fan; Yi-Man Sun; Yue Hu; Wen-Yan Guo; De-Qiang Ji; Hong-Jun Wu; De-Bin Ji (Chemical Engineering Journal, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Seasonal study of interactive cascade ventilation: Parametric analysis for energy efficiency and thermal comfort - Haiyang Sun; Han Li; Xiangfei Kong; Zhaoying Wang; Man Fan (Building and Environment, 2026)

Deciphering the role and mechanism of biochar dosage and inoculum-to-substrate ratio in modulating interspecies electron transfer and alleviating acid inhibition - Yu-Hong Qiu; Zi-Fan Wu; Jia-Bing Li; Zhi-Man Yang (Biomass and Bioenergy, 2026)

Improving the presentation of HONO in CMAQ based on observations over the Yangtze River Delta Region - Shuxian Zhang; Jie Yao; Honghui Xu; Jun He; Man Yue; Meng Shan; Fan Meng; Xiaoai Jin; Ziqi Jin; Huansang Chen; Yilei Dong (Atmospheric Research, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

New insights for microplastic degradation: Synergistic degradation mechanisms of microplastics and atrazine in sediments - Cheng Yang; Jinjiang Duan; Jianhao Song; Yu Xiang; Ruxin Yang; Xiangtian Man; Yuanyuan Feng; Dongdong Gao; Mengli Chen; Qingping Zou; Meikun Fan; Han Zhang (Water Research, 2025)

Efficient removal of microplastics through a combined treatment process: Pre-filtration and adsorption - Bo Lv; Wen Fan; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Journal of Environmental Management, 2025)

Dual-nitrogen-source anchored biochar achieves efficient removal of Cr(VI) from wastewater through an adsorption-reduction coupling mechanism - Xue-Qi Fan; Yi-Man Sun; Le Tao; Shu-Xia Guan; De-Bin Ji (Journal of Environmental Chemical Engineering, 2025)

Bilayer Bifidobacterium animalis/xylooligosaccharides film enables long-term maintenance of probiotics activity and prolongs strawberry shelf life - Haoxin Li; Xingyu Fan; Man Zhou; Li Chen; Xiaojie Yu; Cunshan Zhou; Haile Ma (Food Packaging and Shelf Life, 2025)

Lipid metabolism homeostasis and low-level glycogen metabolism in the Harderian gland of hibernating Daurian ground squirrels - Lu-Fan Li; Yu-Jing Yan; Yi-Man Liu; Qing-Ying Wang; Ming-Di Wang; Jin-Hui Xu; Zhe Wang (Cryobiology, 2025)

Thymus serpyllum extract exerts anticancer activities against colorectal cancer by modulating metastasis, cell cycle arrest, and apoptosis - Chao-Yuan Yao; Kai-Fu Chang; Ju-Huei Chien; Xiao-Fan Huang; Yu-Chi Chen; Ming-Chang Hsieh; Nu-Man Tsai (Molecular Biology Reports, 2025)

Proteomic Signatures of Dental Enamel Hypomineralization: Divergent Molecular Pathways in Coal-Burning vs. Drinking-Water Fluorosis - Na Yang; Jiabing Fan; Guobao Man; Wentai Wang; Jian Liao; Chenglong Tu (Biological Trace Element Research, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Solar cities: Multiple-reflection within urban canyons - Fan Xu; Man Sing Wong; Rui Zhu; Ying Dang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Role and mechanism of combination of biochar and electroactive microbial consortium in facilitating methanogenesis - Kai-Zhao Wang; Zi-Fan Wu; Yu-Hong Qiu; Zhi-Man Yang (Chemical Engineering Journal, 2025)

Coupled dynamic modeling and analysis for collecting asteroid soil using a flexible brush sampler - Qichen Sun; Bolin Zhang; Bo Lei; Fan Guo; Jianfeng Man; Jinyang Liu; Zeng Zhao (Advances in Space Research, 2025)

A plant virus causes symptoms through the deployment of a host-mimicking protein domain to attract the insect vector - Man Gao; Emmanuel Aguilar; Borja Garnelo Gómez; Laura Medina-Puche; Pengfei Fan; Irene Ontiveros; Shaojun Pan; Huang Tan; Hua Wei; Edda von Roepenack-Lahaye; Na Chen; Xiao-Wei Wang; et al. (Molecular Plant, 2025)

Lophatherum-Gracile driven near-infrared carbon dots inhibit ferroptosis and mitophagy to treat acute kidney injury - Lijuan Yang; Fan Dai; Haitian Tang; Man Li; Yibo An; Yubo Tan; Renyuan Liu; Xinyu Tan; Wenxiang Zhang; Syed Faheem Askari Rizvi; Junjie Zou; Zhixiang Lu; et al. (Chemical Engineering Journal, 2025)

Hierarchical PVA/SiO₂ hybrid coating constructs superhydrophilic/underwater superoleophobic polypropylene membranes for efficient emulsion separation - Shuang Man; Lin Yang; Xinyue Fan; Jie Chen; Zhengkang Shi; Ming Zhang; MeiTong Li (Journal of Water Process Engineering, 2025)

Assessing microplastic and nanoplastic contamination in bird lungs: evidence of ecological risks and bioindicator potential - Mengzhu Wang; Pinxi Zhou; Shane DuBay; Shangmingyu Zhang; Zhixiong Yang; Yibo Wang; Jiayu Zhang; Yiwei Cao; Zhengrui Hu; Xingcheng He; Shirui Wang; Man Li; et al. (Journal of Hazardous Materials, 2025)

miR-629-3p inhibits fine particulate matter exposure-induced lung function decline: Results from the two-stage population study and in vitro study - Min Zhou; Xiaojie You; Jiake Zhang; Zi Ye; Jiahao Song; Bingdong Chen; Lieyang Fan; Jixuan Ma; Shijie Yang; Man Cheng; Weihong Chen (Environmental Pollution, 2025)

Experimental research on human thermal sensitivity and thermal demand distribution in regional regulatory environments - Han Li; Zhiyao Wu; Haiyu Hu; Xiangfei Kong; Man Fan (Building and Environment, 2025)

Experimental research on energy utilization, aerosol transmission and thermal comfort under different ventilation strategies: Densely-occupied classrooms as a case study - Han Li; Musong Liu; Xiangfei Kong; Leilei Wang; Jinchao Li; Man Fan (Building and Environment, 2025)

Mixing characteristics and co-flow behavior in interactive cascade ventilation: An experimental approach - Han Li; Ruoyi Liu; Xiangfei Kong; Leilei Wang; Jinchao Li; Man Fan (Building and Environment, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

H-zeolite supported multi-interface metal catalysts for the catalytic destruction of chlorinated organics - Pengfei Sun; Si Chen; Man Xie; Lujun Cheng; Jiasheng Wang; Fan Dong; Xiaoping Dong; Xiaole Weng (Chemical Engineering Journal, 2025)

Change of morphology of rice derived spherical hydrochar during activation - Shuaizhi Man; Kai Sun; Shu Zhang; Mengjiao Fan; Xun Hu (Journal of Environmental Chemical Engineering, 2024)

Functionalized construction of multiple active centers for durability controlling during catalytic combustion of chlorinated aromatic hydrocarbons - Lujun Cheng; Si Chen; Man Xie; Lu Fang; Pengfei Sun; Fan Dong; Xiaoping Dong (Chemical Engineering Journal, 2024)

Incorporation of laser-induced graphene with hierarchical NiCo layered double hydroxide nanosheets for electrochemical determination of glucose in food and serum - Man Huang; Lei Ye; Liwen Yu; Yuanyuan Zhang; Ting Zeng; Juan Yang; Fan Tian; Zhen Wu; Xiuhua Zhang; Chengguo Hu; Nianjun Yang (Analytica Chimica Acta, 2024)

Polystyrene nanoplastics induce lipophagy via the AMPK/ULK1 pathway and block lipophagic flux leading to lipid accumulation in hepatocytes - Zhuying Fan; Yukang Zhang; Yuting Fang; Huiyuan Zhong; Tingting Wei; Huraira Akhtar; Jiahuai Zhang; Man Yang; Yanbo Li; Xianqing Zhou; Zhiwei Sun; Ji Wang (Journal of Hazardous Materials, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Optimized air-ground data fusion method for mine slope modeling - Dan Liu; Man Huang; Zhigang Tao; Chenjie Hong; Yuewei Wu; En Fan; Fei Yang (Journal of Mountain Science, 2024)

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Over 30% external quantum efficiency for doping-free D-A-type thermally activated delayed fluorescence organic light-emitting diodes - Yang Li; Yixia Liu; Yang Gao; Kai Zhang; Yan-Qiu Sun; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2024)

A simple molecular design strategy for efficient deep-red thermally activated delayed fluorescence emitter - Yu-Xin Jin; Huanling Liu; Yue Zhao; Zi-Qi Chen; Shengkai Hu; Kai Zhang; Man-Keung Fung; Dong-Ying Zhou; Liang-Sheng Liao; Jian Fan (Chemical Engineering Journal, 2024)

Experimental study on the cross-infection control performance under intervention cascade ventilation in the post-epidemic era - Han Li; Yuer Lan; Zhaoying Wang; Xiangfei Kong; Man Fan (Sustainable Cities and Society, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Nickel foam based monolithic catalyst supporting transition metal oxides for toluene combustion: Experimental and theoretical study of interfacial synergistic oxidation and water resistance - Pengfei Sun; Lujun Cheng; Si Chen; Man Xie; Fan Dong; Xiaoping Dong (Chemical Engineering Journal, 2024)

Integrated analysis of natural glycans using a versatile pyrazolone-type heterobifunctional tag ANPMP - Yuxia Liu; Tong Yang; Jinqiao Rong; Jinhang Yuan; Lijuan Man; Ming Wei; Jiangbo Fan; Yao Lan; Yinchuan Liu; Guiping Gong; Yu Lu; Xuezheng Song; et al. (Carbohydrate Polymers, 2024)

Niacin alleviates extracellular matrix deposition in ethanol + CCl4-induced liver fibrosis through the HSP90/JAK1/STAT3 axis - Yanping Fan; Meilan Xue; Tianhu Shan; Yixian Bai; Huaqi Zhang; Man Liu; Peng Wang; Xi Liang; Hui Liang (Food Bioscience, 2024)

Study on the infection control performance under interactive cascade ventilation: A focus on a conference room environment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Comparative study on the thermal characteristics under different air distribution strategies oriented to non-uniform environment: An indoor experiment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2023)

A robust and flexible satellite aerosol retrieval algorithm for multi-angle polarimetric measurements with physics-informed deep learning method - Minghui Tao; Jinxi Chen; Xiaoguang Xu; Wenjing Man; Lina Xu; Lunche Wang; Yi Wang; Jun Wang; Meng Fan; Muhammad Imran Shahzad; Liangfu Chen (Remote Sensing of Environment, 2023)

Role and mechanism of WNT5A in benzo(a)pyrene-induced acute lung injury and lung function decline - Lieyang Fan; Bin Wang; Jixuan Ma; Zi Ye; Xiuquan Nie; Man Cheng; Yujia Xie; Pei Gu; Yingdie Zhang; Xiaojie You; Yun Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Experimental study on the influence of environmental parameters on human multi-node warming sensitivity and demand - Han Li; Haiyu Hu; Xiangfei Kong; Man Fan (Building and Environment, 2023)

Simultaneous detection of multiple influenza virus subtypes based on microbead-encoded microfluidic chip - Shao-Li Hong; Xuan Wang; Zhong-Hua Bao; Meng-Fan Zhang; Man Tang; Nangang Zhang; Huihong Liu; Zi-Yuan Zhu; Kan Liu; Zhi-Liang Chen; Wei Li (Analytica Chimica Acta, 2023)

Electrical conductivity-based assessment method for semi-clathrate hydrate conversion and phase change characteristics in gas capture and energy storage - Fan Wang; Yuan Lv; Xinran Xia; Man Li; Chuanxiao Cheng; Wenfeng Hu; Lunxiang Zhang; Lei Yang; Jiafei Zhao; Yongchen Song (Journal of Cleaner Production, 2023)

Experimental research on the cross-infection control performance of different ventilation strategies - Han Li; Yuer Lan; Musong Liu; Xiangfei Kong; Man Fan (Building and Environment, 2023)

Experimental study on human multi-node thermal sensitivity and thermal demand oriented to uniform environment - Han Li; Haiyu Hu; Xiangfei Kong; Man Fan (Building and Environment, 2023)

Semantic segmentation of urban building surface materials using multi-scale contextual attention network - Fan Xu; Man Sing Wong; Rui Zhu; Joon Heo; Guoqiang Shi (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of low temperature on the resistance of Listeria monocytogenes and Escherichia coli O157:H7 to acid electrolyzed water - Man Yu; Chunling Jiang; Yuanyuan Meng; Fan Wang; Jiang Qian; Fulin Fei; Zhenjie Yin; Wei Zhao; Yong Zhao; Haiquan Liu (Food Research International, 2023)

The potential role of plasma miR-4301 in PM2.5 exposure-associated lung function reduction - Jiahao Song; Man Cheng; Bin Wang; Min Zhou; Zi Ye; Lieyang Fan; Linling Yu; Xing Wang; Jixuan Ma; Weihong Chen (Environmental Pollution, 2023)

An unusual occurrence of hydroxylated isoprenoid GDGTs in forest soils - Yi Man; Jiachen Fan; Miao Huang; Huan Yang (Organic Geochemistry, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

A facile method to achieve red thermally activated delayed fluorescence emitters with EQE over 30% via molecular aspect ratio engineering - Jing-Xing Liang; Ze-Hui Pan; Kai Zhang; Dezhi Yang; Jing-Wen Tai; Chuan-Kui Wang; Man-Keung Fung; Dongge Ma; Jian Fan (Chemical Engineering Journal, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Analysis on the thermal performance of low-temperature radiant floor coupled with intermittent stratum ventilation (LTR-ISV) for space heating - Xiangfei Kong; Yufan Chang; Man Fan; Han Li (Energy and Buildings, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

The structures and applications of microbial chondroitin AC lyase - Xiao-Man Fan; Li-Jian Zhou; Jia-Ying Huang; Ye-Wang Zhang (World Journal of Microbiology and Biotechnology, 2022)

Long-term straw return increases biological nitrogen fixation by increasing soil organic carbon and decreasing available nitrogen in rice–rape rotation - Huishan Fan; Shengqiang Jia; Man Yu; Xijing Chen; Alin Shen; Yao Su (Plant and Soil, 2022)

Dolominol a and B, two new neolignans from Dolomiaea souliei (Franch.) C.Shih - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Jing-Xin Mao; Guowei Wang; Mingxing Liu; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

High-throughput “read-on-ski” automated imaging and label-free detection system for toxicity screening of compounds using personalised human kidney organoids - Qizheng Wang; Jun Lu; Ke Fan; Yiwei Xu; Yucui Xiong; Zhiyong Sun; Man Zhai; Zhizhong Zhang; Sheng Zhang; Yan Song; Jianzhong Luo; Mingliang You; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Rubus chingii var. suavissimus alleviates high-fat diet-induced lipid metabolism disorder via modulation of the PPARs/SREBP pathway in Syrian golden hamsters - Man-Jing Jiang; Li Li; Wan-Fang Huang; Jian Su; Yao-Hua Li; Xiao-Sheng Qu; Lan-Lan Fan (Journal of Natural Medicines, 2021)

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A Spatiotemporal Statistical Method of Ship Domain in the Inland Waters Driven by Trajectory Data - Fan Zhang; Xin Peng; Liang Huang; Man Zhu; Yuanqiao Wen; Haitao Zheng (Journal of Marine Science and Engineering, 2021)
In this study, a method for dynamically establishing ship domain in inland waters is proposed to help make decisions about ship collision avoidance. The surrounding waters of the target ship are divided to grids and then calculating the grid densities of ships in each moment to determine the shape and size of ship domain of different types of ships. At last, based on the spatiotemporal statistical method, the characteristics of ship domains of different types of ship in different navigational environments were analyzed. The proposed method is applied to establish ship domains of different types of ship in Wuhan section of the Yangtze River in January, February, July, and August in 2014. The results show that the size of ship domain increases as the ship size increases in each month. The domain size is significantly influenced by the water level, and the ship domain size in dry seasons is larger than in the wet seasons of inland waters.

Fetal growth, fetal development, and placental features in women with polycystic ovary syndrome: analysis based on fetal and placental magnetic resonance imaging - Qing Zhang; Zhong-kun Bao; Mei-xiang Deng; Qiong Xu; Dan-dan Ding; Man-man Pan; Xi Xi; Fang-fang Wang; Yu Zou; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2020)

Chemical constituents from common vetch ( Vicia sativa L.) and their antioxidant and cytotoxic activities - Li-Fang Liu; Wen-Hai Li; Man-Yu Li; Xiao-Zhen Wu; Fan Yang; Jia-Nan Xu; Cheng-Shan Yuan (Natural Product Research, 2020)

Effects of Cedrus atlantica extract on acute myeloid leukemia cell cycle distribution and apoptosis - Pei-Hsiu Hung; Ming-Chang Hsieh; Shan-Chih Lee; Xiao-Fan Huang; Kai-Fu Chang; Szu-Yin Chen; Ming-Shih Lee; Nu-Man Tsai (Molecular Biology Reports, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Aging exacerbates impairments of cerebral blood flow autoregulation and cognition in diabetic rats - Shaoxun Wang; Wenshan Lv; Huawei Zhang; Yedan Liu; Longyang Li; Joshua R. Jefferson; Ya Guo; Man Li; Wenjun Gao; Xing Fang; Ian A. Paul; Grazyna Rajkowska; et al. (GeroScience, 2020)

Circulating Selenium and Cardiovascular or All-Cause Mortality in the General Population: a Meta-Analysis - Shouyan Xiang; Zhe Dai; Changfeng Man; Yu Fan (Biological Trace Element Research, 2020)

A new neolignan glycoside from Dolomiaea souliei - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Yun-Yi Tao; Zhi-Hua- Liao; Min Chen (Natural Product Research, 2020)

Rethinking labelling in road segmentation - Man Yuan; Zhi Liu; Fan Wang; Fei Jin (International Journal of Remote Sensing, 2019)

Integrated analysis of mRNA-seq and miRNA-seq for host susceptibilities to influenza A (H7N9) infection in inbred mouse lines - Suying Bao; Lilong Jia; Xueya Zhou; Zhi-Gang Zhang; Hazel Wai Lan Wu; Zhe Yu; Gordon Ng; Yanhui Fan; Dana S. M. Wong; Shishu Huang; Kelvin Kai Wang To; Kwok-Yung Yuen; et al. (Functional & Integrative Genomics, 2018)

Differential expression of hormone related genes between extreme segregants of a Saccharum interspecific F2 population - Fan Zhu; Ching Man Wai; Jisen Zhang; Tyler C. Jones; Chifumi Nagai; Ray Ming (Euphytica, 2018)

Verrucosispora rhizosphaerae sp. nov., isolated from mangrove rhizosphere soil - Qing-yi Xie; Xiao-dong Bao; Qing-yu Ma; Fan-dong Kong; Man-li Zhou; Bing Yan; You-xing Zhao (Antonie van Leeuwenhoek, 2018)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Retraction Note to: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Numerical simulation on the effects of drug-eluting stents with different bending angles on hemodynamics and drug distribution - Yu Chen; Yan Xiong; Wentao Jiang; Man Sang Wong; Fei Yan; Qingyuan Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2016)

RETRACTED ARTICLE: BMP2-Smad-Mediated SH-SY5Y Neuroblastoma Cell Proliferation and Neurite Outgrowth Are Regulated Through Dynamin-Dependent Endocytosis - Xiangshan Yang; Shunzeng Lv; Daotang Li; Wenyuan Lv; Kaixi Fan; Lijun Sheng; Ranran Shi; Jing Zhang; Man Feng; Zhongfa Xu (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Elevated homocysteine levels and risk of cardiovascular and all-cause mortality: a meta-analysis of prospective studies - Hui-yong Peng; Chang-feng Man; Juan Xu; Yu Fan (Journal of Zhejiang University-SCIENCE B, 2015)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Identification of quantitative trait loci across interspecific F2, F2:3 and testcross populations for agronomic and fiber traits in tetraploid cotton - Jiwen Yu; Shuxun Yu; Michael Gore; Man Wu; Honghong Zhai; Xingli Li; Shuli Fan; Meizhen Song; Jinfa Zhang (Euphytica, 2013)

A Rhodamine-Cyclen Conjugate as Chromogenic and Fluorescent Chemosensor for Copper Ion in Aqueous Media - Min Wang; Di Zhang; Man Li; Min Fan; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2013)

Molecular characterization of Japanese encephalitis viruses circulating in pigs and mosquitoes on pig farms in the Chinese province of Henan - Man Teng; Jun Luo; Jian-Ming Fan; Lu Chen; Xing-Tao Wang; Wu Yao; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2013)

Mapping quantitative trait loci for lint yield and fiber quality across environments in a Gossypium hirsutum × Gossypium barbadense backcross inbred line population - Jiwen Yu; Ke Zhang; Shuaiyang Li; Shuxun Yu; Honghong Zhai; Man Wu; Xingli Li; Shuli Fan; Meizhen Song; Daigang Yang; Yunhai Li; Jinfa Zhang (Theoretical and Applied Genetics, 2013)

Deterioration of Stress Distribution Due to Tunnel Creation in Single-Bundle and Double-Bundle Anterior Cruciate Ligament Reconstructions - Jie Yao; ChunYi Wen; Jason Tak-Man Cheung; Ming Zhang; Yong Hu; Chunhoi Yan; Kwong-Yuen Peter Chiu; William Weijia Lu; Yubo Fan (Annals of Biomedical Engineering, 2012)

Improved drought and salt tolerance of Arabidopsis thaliana by transgenic expression of a novel DREB gene from Leymus chinensis - Peng Xianjun; Ma Xingyong; Fan Weihong; Su Man; Cheng Liqin; Iftekhar Alam; Byung-Hyun Lee; Qi Dongmei; Shen Shihua; Liu Gongshe (Plant Cell Reports, 2011)

Erratum to: Marek’s disease virus-encoded microRNAs: genomics, expression and function - Jun Luo; Man Teng; JianMing Fan; FangYu Wang; Ling Zhou; RuiGuang Deng; GaiPing Zhang (Science China Life Sciences, 2010)

Marek’s disease virus-encoded microRNAs: genomics, expression and function - Jun Luo; Man Teng; JianMing Fan; FangYu Wang; Ling Zhou; RuiGuang Deng; GaiPing Zhang (Science China Life Sciences, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Characterization of SARS-CoV-specific memory T cells from recovered individuals 4 years after infection - Yan-Ying Fan; Zi-Tong Huang; Li Li; Man-Hui Wu; Tao Yu; Richard A. Koup; Robert T. Bailer; Chang-You Wu (Archives of Virology, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Influence of ginsenoside Rg1, a panaxatriol saponin from Panax notoginseng, on renal fibrosis in rats with unilateral ureteral obstruction - Xi-sheng Xie; Man Yang; Heng-cuang Liu; Chuan Zuo; Zi Li; Yao Deng; Jun-ming Fan (Journal of Zhejiang University-SCIENCE B, 2008)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

Effect of postmenopausal hormone replacement therapy on lipoprotein and homocysteine levels in Chinese women - Ricky Y.K. Man; Lily K.F. Ting; Susan Fan; Maggie M.H. Lau; Yaw L. Siow; Yee H. Chung; O. Karmin (Molecular and Cellular Biochemistry, 2001)